2019
DOI: 10.4103/ijo.ijo_1699_18
|View full text |Cite
|
Sign up to set email alerts
|

A report of orbital metastasis from a urinary bladder adenocarcinoma

Abstract: A 60-year-old man presented with sudden-onset proptosis of the left eye and intermittent diplopia of 2 months duration. Ophthalmic examination revealed bilateral eyelid retraction, left eye proptosis and a firm, non-tender mass (2 cm × 1.5 cm) in left supero-medial orbit with restricted extraocular movements. Contrast-enhanced computed tomography showed a well-defined, enhancing antero-medial orbital mass which was removed via anterior orbitotomy approach. The histopathology/immunohistochemistry showed adenoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…Te primary site of orbital metastasis can vary widely. Previous reports have suggested that prostate and lung carcinomas are common primary sites in males, whereas in females, breast carcinoma tops the list [7]. Te clinical manifestations of orbital metastases vary.…”
Section: Introductionmentioning
confidence: 99%
“…Te primary site of orbital metastasis can vary widely. Previous reports have suggested that prostate and lung carcinomas are common primary sites in males, whereas in females, breast carcinoma tops the list [7]. Te clinical manifestations of orbital metastases vary.…”
Section: Introductionmentioning
confidence: 99%